The Political Costs of Oil Price Shocks - Rabah Arezki; Simeon Djankov; Ha Nguyen; Ivan Yotzov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We explore the effect of oil import price shocks on political outcomes using a worldwide dataset on elections of chief executives. Oil import price shocks cause a reduction in the odds of reelection of incumbents, an increase in media chatter about fuel prices, and an increase in non-violent protests. These results are present in democracies but absent in autocracies. To explain the dichotomy, we show that the pass-through from international to domestic fuel prices is limited in autocracies with adverse consequences on levels of debt and international reserves. The results point to the interdependence of goods markets and politics.
Keywords: D72; E21; P16; Q43; 330; elections; democracy; autocracy; incumbent; oil prices; economic shocks